Marinegeohazards project – an early warning system in the BLACK SEA - Ranguelov, Boyko; Mardirossian, Garo; Marinova, Nadia (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The general frame of the BG-ROM MARINEGEOHAZARDS Project is considered. The Project is about set-up and implementation of the key core components of a regional early-warning system for marine geohazards of risk to the Romanian-Bulgarian Black Sea costal area The main focus is on the data and informa-tion about the investigations related to the creation of the marine geo hazards early warning system. The target topics are on the earthquakes, landslides, tsunamis, floods and similar natural hazards. Maps and schemas about the main hazards have been created for the Bulgaria-Romania cross border area – both in marine and coastal environment. The typology and quantification of the hazards and their dangerous elements support the key core elements selection and the infrastructure of the early warning system targeted to the population and society safety.